A new iterative linearization approach for solving nonlinear equations systems - Temelcan, Gizem; Sivri, Mustafa; Albayrak, Inci (RAMAZAN YAMAN, 2020)
Nonlinear equations arise frequently while modeling chemistry, physics, econ- omy and engineering problems. In this paper, a new iterative approach for finding a solution of a nonlinear equations system (NLES) is presented by applying a linearization technique. The proposed approach is based on com- putational method that converts NLES into a linear equations system by using Taylor series expansion at the chosen arbitrary nonnegative initial point. Us- ing the obtained solution of the linear equations system, a linear programming (LP) problem is constructed by considering the equations as constraints and minimizing the objective function constructed as the summation of balanc- ing variables. At the end of the presented algorithm, the exact solution of the NLES is obtained. The performance of the proposed approach has been demonstrated by considering different numerical examples from literature.
Keywords: Nonlinear equations system; Linear programming problem; Taylor series; ALGORITHM; FAMILY; Mathematics